2015
DOI: 10.3390/nu7075231
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability and Validity of the Perceived Dietary Adherence Questionnaire for People with Type 2 Diabetes

Abstract: Nutrition therapy is essential for diabetes treatment, and assessment of dietary intake can be time consuming. The purpose of this study was to develop a reliable and valid instrument to measure diabetic patients’ adherence to Canadian diabetes nutrition recommendations. Specific information derived from three, repeated 24-h dietary recalls of 64 type 2 diabetic patients, aged 59.2 ± 9.7 years, was correlated with a total score and individual items of the Perceived Dietary Adherence Questionnaire (PDAQ). Test-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 29 publications
(43 reference statements)
0
61
0
Order By: Relevance
“…• α = 0.05; Zα = 1.96; β = 0.2; Zβ = 0.842 • r = 0.3 (according to Asaad et al [36], the obtained correlation between fruits and vegetable servings, high sugar foods and high fiber foods obtained from the perceived dietary adherence questionnaire and the 24 h recalls were 0.30, 0.40 and 0.46, respectively. Other correlations were not considered, as they were irrelevant in our case, e.g., low glycemic index foods)…”
Section: Inclusion Criteria and Sampling Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…• α = 0.05; Zα = 1.96; β = 0.2; Zβ = 0.842 • r = 0.3 (according to Asaad et al [36], the obtained correlation between fruits and vegetable servings, high sugar foods and high fiber foods obtained from the perceived dietary adherence questionnaire and the 24 h recalls were 0.30, 0.40 and 0.46, respectively. Other correlations were not considered, as they were irrelevant in our case, e.g., low glycemic index foods)…”
Section: Inclusion Criteria and Sampling Methodsmentioning
confidence: 89%
“…These findings differ from those in other studies. Hoelscher, Day, Kelder and Ward [39] reported that the percentage agreement between the School-Based Nutrition Monitoring questionnaire and the 24 h recall ranged from 38% to 89%, and Asaad, Sadegian, Lau, Xu, Soria-Contreras, Bell and Chan [36] reported that six out of nine items (67%) of the Perceived Dietary Adherence Questionnaire designed for diabetic patients were significantly correlated with the 24 h recall. However, the current study showed no significant correlation between the DAQ and the dietary recall for the items regarding skimmed milk and soft drinks.…”
Section: Correlations Between Scoresmentioning
confidence: 99%
“…The reliability coefficient of the questionnaire was then calculated by 0.91. As well, scores from 1 to 4 were considered (totally disagree 1, disagree 2, agree 3, totally agree 4) for the questionnaire items based on a 4-point Likert-type scale.The fourth part of the questionnaire was Perceived Dietary Adherence Questionnaire (PDAQ) focused on proper dietary adherence whose validity and reliability had been examined by Asaad et al [27] in the Canadian population in 2015. The given questionnaire included 9 items based on the Canadian Diabetes Association’s Clinical Nutrition Guidelines designed and extracted from Canada’s Food Guide.…”
Section: Methodsmentioning
confidence: 99%
“…Diet quality was assessed by calculating the Healthy Eating Index (HEI) adapted to the Canadian population [26]. Participants’ perceptions of their dietary adherence to CDA Nutrition Therapy Guidelines were assessed by the Perceived Dietary Adherence Questionnaire (PDAQ) [27]. Prior to and post-intervention, participants were asked to report all the medications that they used (name of drug, frequency of use and dose) as a potential confounder of intervention outcomes.…”
Section: Methodsmentioning
confidence: 99%